2020
DOI: 10.2320/matertrans.mt-mn2019013
|View full text |Cite
|
Sign up to set email alerts
|

Ab-Initio Study on Structural and Magnetic Properties of Fe-Doped MnCoGe

Abstract: First-principles calculations were performed to investigate the effect of Fe substitution on the structural transformation of (Mn,Fe)CoGe and Mn(Co,Fe)Ge. The activation energy (barrier) between orthorhombic and hexagonal structures was estimated from the total energy of each of several virtual structures between them.Fe substitution reduces the activation energy, and movements of both of Co and Mn are closely related to the reduction. Moreover, the calculation result for the Fe substitution at the sites of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The data for x = 0.25 are the results reported in Ref. 4). It can be seen that ¦E decreases with an increase of x in all cases of Cu or Fe partial substitution for the Mn site or the Co site or both sites.…”
Section: Change Of ¦Ementioning
confidence: 88%
See 1 more Smart Citation
“…The data for x = 0.25 are the results reported in Ref. 4). It can be seen that ¦E decreases with an increase of x in all cases of Cu or Fe partial substitution for the Mn site or the Co site or both sites.…”
Section: Change Of ¦Ementioning
confidence: 88%
“…Until now, we have investigated the effects of Cu and Fe partial substitution on lattice constants, interatomic distances, activation energies (energy barrier between two structures), and so on. 3,4) Tran et al 5,6) investigated the magnetocaloric effect of MnCoGe 1¹x Cu x and Mn 1¹x Cu x CoGe by combining of the DFT calculations and Monte-Carlo simulations, and quantitatively reproduced the giant isothermal magnetic entropy changes. Liu et al 7) experimentally showed that a second-order magnetic transition with negligible thermal hysteresis and a large magnetization change can be realized in Mn 1¹x Cu x CoGe and discussed the experimental results from chemical bonds and the magnetic exchange interaction estimated by the DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…They discuss a method to identify orientations of pairs of facets, which can form on an arbitrary crystal orientation. In the second paper, 161) structural and magnetic properties of Fe-doped MnCoGe were studied by using the first principles calculations within the density functional theory level. They found Fe substitution reduces the barrier energy from orthorhombic to hexagonal structures, which have strong correlation with the movements of both of Co and Mn.…”
Section: Computational Materials Sciencementioning
confidence: 99%